Possible Alternative Dispute Resolution Processes to Prevent Trade Wars in the WTO Appellate Body: Issues and Challenges - Afsin Sultana Ami (Dhaka University Law Journal, 2025)
The 2018 US-China trade war and the escalating 2023 trade war between the two major actors, the US and China, are just two examples of the numerous trade crises the globe is currently experiencing. The trade war has left the entire world in doubt. The GATT/WTO attempts to control these trade conflicts continuously, but without a suitable dispute settlement forum, it is impossible to regulate these arbitrary trade conflicts effectively. The World Trade Organisation (WTO) has a dedicated dispute resolution forum. The issue is that the US has been utilising the positive consensus requirement to prevent the appointment of judges to the Appellate Body for the previous few years. The problem is that, although there is an appellate body, no one is present to make a decision. The losing party, therefore, can appeal against the panel’s decision and leave the fate of the dispute uncertain forever. Therefore, WTO members, aware of this crisis, take the greatest unfair advantage of it. The research, therefore, argues that the crisis is there, but there are several alternatives through which it is possible to regulate trade wars. To this purpose, it attempts to argue that there are sufficient incentives which will, in the end, compel the states to cooperate amid the alternative approaches. Dhaka University Law Journal, 2025, 36 (1), 123-148